TEHL simulation on the influence of lubricants on load-dependent gear losses. (September 2017) - Ziegltrum, A.; Lohner, T.; Stahl, K.
Abstract: A transient TEHL simulation model based on a finite element formulation and implemented in multiphysics software is applied to study the TEHL contact along the path of contact of spur gears with a focus on load-dependent gear loss of different lubricants. Lubricant properties including the limiting shear stress are based on measurement data. The considered polyalphaolefin and polyglycol oil show significant lower fluid coefficients of friction, maximum TEHL temperatures and local gear power losses than the considered mineral oil. The simulated load-dependent gear power losses of the mineral oil are compared to the measured load-dependent gear power losses in the FZG gear efficiency test rig. Results show very strong correlation when taking into account mixed lubrication. Highlights: TEHL simulation was used to study load-dependent gear loss of lubricants. Transient FE based TEHL simulation model in multiphysics software was applied to spur gears. Lubricant properties including limiting shear stress were based on measurement data. Strong correlation of simulated and measured load-dependent gear loss was shown for mineral oil. Load-dependent gear loss was significantly reduced by polyalphaolefin and polygycol oil.